Epithelial Cell Coculture Models for Studying Infectious Diseases: Benefits and Limitations. (5th October 2011) - Duell, Benjamin L.; Cripps, Allan W.; Schembri, Mark A.; Ulett, Glen C.
Abstract : Countless in vitro cell culture models based on the use of epithelial cell types of single lineages have been characterized and have provided insight into the mechanisms of infection for various microbial pathogens. Diverse culture models based on disease-relevant mucosal epithelial cell types derived from gastrointestinal, genitourinary, and pulmonary organ systems have delineated many key host-pathogen interactions that underlie viral, parasitic, and bacterial disease pathogenesis. An alternative to single lineage epithelial cell monoculture, which offers more flexibility and can overcome some of the limitations of epithelial cell culture models based on only single cell types, is coculture of epithelial cells with other host cell types. Various coculture models have been described, which incorporate epithelial cell types in culture combination with a wide range of other cell types including neutrophils, eosinophils, monocytes, and lymphocytes. This paper will summarize current models of epithelial cell coculture and will discuss the benefits and limitations of epithelial cell coculture for studying host-pathogen dynamics in infectious diseases.